2008
DOI: 10.1002/bies.20729
|View full text |Cite
|
Sign up to set email alerts
|

Dental enamel as a dietary indicator in mammals

Abstract: The considerable variation in shape, size, structure and properties of the enamel cap covering mammalian teeth is a topic of great evolutionary interest. No existing theories explain how such variations might be fit for the purpose of breaking food particles down. Borrowing from engineering materials science, we use principles of fracture and deformation of solids to provide a quantitative account of how mammalian enamel may be adapted to diet. Particular attention is paid to mammals that feed on 'hard objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
272
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(290 citation statements)
references
References 77 publications
9
272
0
9
Order By: Relevance
“…Furthermore, Lucas et al. (2008) have shown that large hard particles have the potential to fracture enamel, whereas small hard particles can only indent it. As such, independently of texture complexity, wear (defined as the loss of tooth tissue) would be greater with large particles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lucas et al. (2008) have shown that large hard particles have the potential to fracture enamel, whereas small hard particles can only indent it. As such, independently of texture complexity, wear (defined as the loss of tooth tissue) would be greater with large particles.…”
Section: Discussionmentioning
confidence: 99%
“…The association between environmental change and canid predatory behaviour was investigated using the arrangement of the enamel prism bands-known as bands of HunterSchreger (HSB)-as a proxy. The reason is because carnivores that live in open environments consume more intrinsic (bones from carcasses) and extrinsic (grit) hard food items, which relates to heavily folded HSB 28,51,[68][69][70] . Studies of carnivorans demonstrate a link between bone and carcass consumption and increased kleptoparasitism in open habitats because of increased carcass detectability [30][31][32] .…”
Section: U O N a Lp In U S C An Is M Es Om El As Ca Nis Ad Us Tus Cmentioning
confidence: 99%
“…For example, an 50 kg anthropoid is predicted to have a molar enamel volume of 6479 mm 3 , equivalent to a sphere with a 11.5 mm radius (similar to the 10 mm estimate proposed by [102] [102]. Moreover, the toughness of a food scales roughly with the amount of fiber [103]; it is reasonable to consider foods with high toughness as less digestible.…”
Section: Model Architecturementioning
confidence: 72%
“…The proximal mechanisms that cause enamel wear are not well understood [105], but likely include silica or phytoliths found within plant foods, exogenous grit or dirt on the outside of plant foods (or the inside of some insects), and/or tooth-on-tooth wear [104,102,150].…”
Section: State Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation